Modifying defect structures at interfaces for high-performance solid oxide fuel cells. Issue 8 (July 2020) - Kim, Seo Ju; Choi, Mingi; Lee, Jongseo; Lee, Wonyoung
Abstract: Oxygen vacancies are important charged defects in oxide ion conductors for oxygen reduction reactions (ORR). They are important reaction sites because of their high oxygen exchange, incorporation ability, and ionic transport reactivity. Herein, to control the defect concentration on the Gd0.1 Ce0.9 O2-δ (GDC) scaffold, the interface between the electrolyte and the electrode was engineered by a wet-chemical-based infiltration technique which constructed the conformal thin-film-like GDC interlayer (10 nm thickness) with smaller grain size than that of the GDC scaffold. X-ray photoelectron spectroscopy revealed the enriched oxygen vacancies in the infiltrated GDC interlayer with a reduced valence state of Ce. ORR kinetics was substantially improved with the infiltrated GDC interlayer, exhibiting a ∼2-fold decrease in polarization resistance and ∼1.41-fold increase in peak power density (0.072 Ωcm 2 and ∼780 mW/cm 2, respectively) at 650 °C. The defect structures at the interfaces and enhanced performance remained unchanged for 200 h at 650 °C.